Low-dose naltrexone in the treatment of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Issue 4 (2nd October 2019) - Polo, Olli; Pesonen, Pia; Tuominen, Essi
ABSTRACT: Background : Myalgic encephalomyelitis (ME)/chronic fatigue syndrome (CFS) is a common medical condition that limits physical and cognitive functions, with no known effective medical treatment. Methods : We report on the safety and effectiveness data accumulated in clinical practice when treating ME/CFS with low-dose naltrexone (LDN, 3.0 – 4.5 mg/day). The medical records from 218 patients who received ar diagnosis of ME/CFS and LDN treatment during 2010–2014 were retrospectively analyzed. Results : Outcome data were available in 92.2% of patients with an average follow-up time of 1.7 years. A positive treatment response to LDN was reported by 73.9% of the patients. Most patients experienced improved vigilance/alertness and improved physical and cognitive performance. Some patients reported less pain and fever, while 18.3% of patients did not report any treatment response to LDN. Mild adverse effects (insomnia, nausea) were common at the beginning of the treatment. Neither severe adverse effects nor long-term adverse symptoms were reported. Conclusions : The high frequency of treatment response and good safety profile observed in this retrospective open label study could prompt prospective controlled studies to confirm the feasibility of LDN in alleviating ME/CFS symptoms.